املصلحة العامة وضوابطها يف املعامالت املالية والتطبيقات املصرفية املعاصرة The public interest and its regulations in financial transactions and contemporary banking applications - Saleh, Abdulmajid Obaid Hasan; Akbar, Kieren (Department of Fiqh and Usul, Academy of Islamic Studies, University of Malaya, 2023)
The renewal process in Islamic financial and banking thought is continuing, especially concerning the application of maslahah in financial and banking transactions. The paper’s primary aim is to apply the maslahah application to all contracts and transactions while paying little attention to the theoretical framework from a sharia perspective. The researchers examine the combination of theoretical and applied aspects to ensure the application of maslahah in financial transactions and contemporary Banking applications. This paper attempts to provide specific applied transactions in current practices while also explaining the mechanisms and processes based on theories in the application of maslahah.